The warm-hot circumgalactic medium of the Milky Way as seen by eROSITA - Locatelli, N.; Ponti, G.; Zheng, X.; Merloni, A.; Becker, W.; Comparat, J.; Dennerl, K.; Freyberg, M. J.; Sasaki, Manami; Yeung, M. C.H. (Astronomy & Astrophysics, 2024)
The first all-sky maps of the diffuse emission of high ionization lines observed in X-rays by SRG/eROSITA provide an excellent probe for the study of the warm-hot phase (T ∼ 106 K) of the circumgalactic medium (CGM) of the Milky Way. In this work, we analyze the O VIII line detected in the first eROSITA All-Sky Survey data (eRASS1). We fit a sky map made in a narrow energy bin around this line with physical emission models embedded in a 3D geometry in order to constrain the density distribution of the warm-hot gas around the Galaxy, with a focus on mid and high (absolute) Galactic latitudes. By masking out the eROSITA bubbles and other bright, extended foreground sources, we find that an oblate geometry of the warm-hot gas (T ≡ 0.15−0.17 keV), flattened around the Galactic disk with scale height zh ∼ 1−3 kpc, best describes the eRASS1 O VIII map, with most of the observed emission shown as being produced within a few kiloparsecs from the Sun. The additional presence of a large-scale warm-hot spherical halo, while providing a minor contribution to the X-ray emission, accounts for the high O VII absorption column densities detected with XMM-Newton as well as most of the baryon budget of the CGM of the Milky Way. To date, the eROSITA data carry the greatest amount of information and detail of the O VIII CGM intensities, allowing for a significant reduction in the statistical uncertainties of the inferred physical parameters.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Galaxy: general; X-rays: diffuse background